Multidisciplinary approach to the treatment of post-concussion syndrome and post-traumatic stress disorder: integration of psychiatry, psychology, neurology and physical therapy - Sak Леся; Yachnyk Сергій; Kurach Олена (Psychosomatic Medicine and General Practice, 2025)
Post-concussion syndrome and post-traumatic stress disorder are complex medico-psychological conditions frequently observed among military personnel and veterans who have sustained traumatic brain injuries (TBIs) in combat settings. The combination of these disorders results in cognitive and somatic impairments, emotional destabilization, and social maladjustment. A significant proportion of patients remain undiagnosed and inadequately rehabilitated, contributing to the chronicity of symptoms. This article presents an interdisciplinary review of current treatment approaches for PCS and PTSD in military and veteran populations. It explores psychiatric, psychological, neurological, and physical therapy strategies within comprehensive care frameworks. The review synthesizes data from international sources concerning neuropsychological mechanisms, pharmacotherapy, psychotherapy, and physical rehabilitation. Objective. To substantiate the effectiveness of a multidisciplinary approach to the treatment of PCS and PTSD in military personnel and veterans; to define the roles of key professionals within the structure of medico-psychological care; and to outline practical rehabilitation algorithms adapted to the specific needs of the military population. Conclusions. Post-concussion syndrome and post-traumatic stress disorder form a clinically complex comorbid configuration with intertwined neurobiological, psycho-emotional, somatic, and social components. Only a multidisciplinary approach, grounded in the biopsychosocial model, can adequately address the multifaceted needs of these patients. Such an approach requires coordinated input from specialists across disciplines, individualized therapeutic plans, outcome monitoring, and the creation of a safe and supportive rehabilitation environment. Keywords: post-concussion syndrome, post-traumatic stress disorder, multidisciplinary approach, psychotherapy, physical therapy, psychopharmacology